An Updated Real-Time Forecasting System for Marine Environments in the North Indian Ocean - Li, Yineng; Li, Shaotian; Peng, Shiqiu; Zhu, Yuhang; Zhou, Fenghua; Tang, Shilin (Frontiers in Marine Science, 2022)
An updated real-time Experimental Platform of Marine Environment Forecasting system for the North Indian Ocean, called EPMEF-NIO, is introduced in this study. The main changes of the updated system include: 1) besides the eastern Indian Ocean (EIO), the western Indian Ocean (WIO) is added to the regions for weather, surge and wave forecasts, and the horizontal resolutions for the two-domain weather forecast are increased from 24 km and 8 km to 18 km and 6 km; 2) a three-domain-nested wave forecast is added to the system with spatial resolutions of 1/3°, 1/12° and 1/36° for the Indo-Pacific, the EIO and WIO, and the Sri Lanka and northern Arabian Sea regions, respectively; 3) the length of forecast time is increased from 72-h to 120-h. The assessment based on substantial observations shows that the performance of the EPMEF-NIO in weather, wave and storm surge forecasts is promising and robust, with comparable (or even better) forecast skills for typhoons and waves to some other official agencies or reanalysis. This is mainly attributed to some spectacular techniques employed in the system including the simplified Scale-Selective Data Assimilation (SSDA) scheme and the sophisticated dealing with the swell from southern Indian Ocean. Therefore, the EPMEF_NIO can provide valuable information of the marine environment forecasts in the North Indian Ocean region.